Visual Identity for Gong Production Malang - Gunawan, Muhammad Wildan; Happy, Handry Rochmad Dwi (Universitas Ciputra, 2023)
Amidst of nowadays hustle and bustle society, organizing and managing an event is such a tiresome work. Not everyone are able to organize and manage their own events. Then there comes an event organizer service. But the event organizer services are also increasingly widespread, so there must be a identity as differentiator in order to be known in the public. An example is a visual Identity. Gong Production Malang as agency that recently established an event organizer service from traditional dance studio requires visual identity. These visual identities are logo, stationery kits, publication media in the such as banner, x-banner and Instagram feeds, uniform t-shirts and key chain accessories. Aside from being a differentiator, the existence of a visual identity also makes Gong production Malang looks professional and considerable by most people.. It was proven by validation results that shows percentage of 82,58%, which means it was quite successful.